Comparison Between Ranson Criteria And Modified Computed Tomography Severity Index In Predicting The Acute Pancreatitis - Hassan, Ali; Rehman, Sheikh Atiq-Ur-; Alvi, Muhammad Ansar (Biological and Clinical Sciences Research Journal, 2025)
Acute pancreatitis (AP) is a potentially life-threatening condition with a highly variable clinical course. Early prediction of disease severity is essential for guiding management and reducing morbidity and mortality. Various scoring systems are used for this purpose, including Ranson criteria and the Modified Computed Tomography Severity Index (MCTSI), though their comparative accuracy remains debated. Objective: To compare the diagnostic accuracy of Ranson criteria and MCTSI in predicting severe acute pancreatitis using the Revised Atlanta Classification as the reference standard. Methods: This cross-sectional validation study was conducted at the Department of Surgery, Bahawalpur Victoria Hospital, Bahawalpur, from 13 June to 13 October 2025. A total of 125 patients aged 18–80 years with a diagnosis of acute pancreatitis were included through non-probability consecutive sampling. Ranson scores were calculated at admission and after 48 hours, while MCTSI was assessed using contrast-enhanced CT within 48–72 hours. Severity was classified according to the Revised Atlanta Classification (2012). Diagnostic performance, including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy, was calculated for both scoring systems. Results: The mean age of patients was 44.62 ± 13.28 years, with 62.4% males. Gallstones were the most common etiology (57.6%). According to the Revised Atlanta Classification, 18.4% patients had severe AP. Ranson criteria predicted severe disease in 23.2% patients, while MCTSI predicted 28.0%. Ranson score demonstrated sensitivity of 87.0%, specificity of 91.2%, PPV of 69.0%, NPV of 96.9%, and overall accuracy of 90.4%. MCTSI showed higher sensitivity (91.3%) but lower specificity (86.3%), with a PPV of 60.0%, an NPV of 97.8%, and an accuracy of 87.2%. Conclusion: Both Ranson criteria and MCTSI are reliable tools for predicting severe acute pancreatitis. MCTSI provides higher sensitivity, making it useful for early identification of severe cases, whereas the Ranson criteria demonstrate higher specificity and overall accuracy. Their combined use may improve clinical decision-making in resource-limited settings.